Effect of different extraction methods on antioxidant and sensorial properties of pasteurized black soymilk - Suhaimi, Qamarina; Wan Kamarudin, Wan Saidatul Syida; Nizori, Addion; Md Sikin, Adi (Indonesian Food Science and Technology Journal, 2023)
Abstract— The processing methods of black soymilk (BSM) can significantly affect the retention of its bioactive compounds. The effect of cold water (4 ℃, 8 hr) (CWE), hot water (80 ℃, 10 min) (HWE) and alkali water extraction (0.25% NaHCO3, 54 ℃, 10 min) (AWE) of BSM on antioxidant and sensory properties of pasteurized BSM (72 ℃ /10 min) was evaluated over 10 days of storage at 4 ℃. A steep increase in the total phenolic content (TPC) of BSM from HWE was observed over 10 days of storage, although the TPC of that from AWE was steadily the highest. The trend of flavonoids of BSM from HWE was the same as that for TPC, achieving a concentration of 1858.77 mg QAE/100 g after 10 days. The total anthocyanin content was the highest (40.85 mg/100 g) in BSM by HWE at the end of storage. Although the TPC of BSM from all extraction methods increased during storage, the total anthocyanin content showed a decreasing trend. Overall, the DPPH radical scavenging activity of BSM by HWE increased during storage up to 32.19 % on day 10 and a decreasing trend was observed from AWE and CWE. Triangle test showed that there was a significant (p<0.05) sensorial difference among the three extraction methods. The BSM from AWE had the highest score in the 9-hedonic scale for all sensorial parameters after the commercial BSM. Overall, the heat treatment in both HWE and AWE enhanced the antioxidant activity and sensory properties of pasteurized BSM, respectively.